2010
DOI: 10.1007/s12011-010-8727-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Picolinate Supplementation on Growth Performance and Meat Characteristics of Swine

Abstract: The purpose of this study was to evaluate the effect of supplemental chromium (Cr) in the form of chromium picolinate (CrPic) on swine growth performance, meat quality, and protein deposition in skeletal muscle. Forty-eight piglets were divided into three groups randomly, fed with three different dietary levels of Cr (common basal feedstuff supplemented with a dose of 1.61 μg/g or 3.22 μg/g CrPic, which corresponded to 0.2 and 0.4 μg/g Cr). Results indicated that during the growing period (1-35 days), pigs fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
4
13
2
8
Order By: Relevance
“…O’Quinn et al (1998) reported that drip loss percentage in gilts increased with increased CrNic supplementation. Zhang et al (2011) reported that no change occurred in water-holding capacity, which was similar to our results. The SF was impacted by several factors such as pH, IMF and storage time of pork longissimus muscle (Van Laack et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…O’Quinn et al (1998) reported that drip loss percentage in gilts increased with increased CrNic supplementation. Zhang et al (2011) reported that no change occurred in water-holding capacity, which was similar to our results. The SF was impacted by several factors such as pH, IMF and storage time of pork longissimus muscle (Van Laack et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Evock-Clover et al (1993) reported that young growing pigs given Cr showed no improvement in growth rate, feed efficiency or composition of gain. Finally, Zhang et al (2011) reported that a supplementary dose of 0.2 mg/kg Cr as chromium picolinate significantly improved daily weight gain during the finishing period, which was similar to our results. We demonstrated that dietary Cr supplementation increased ADG but that the feed utilization of growing-finishing pigs decreased with the increasing Cr supplementation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The shear force of cooked meat has been proved to decrease with increasing intramuscular fat contents and pH 1 value [42], but neither was affected by CrMet addition in present experiment. Besides, our data revealed that the moisture, crude fat, and protein contents in muscle were not affected by CrMet, which agreed with the results of Zhang et al [43], who used 200, 400 μg/kg chromium as CrPic in growingfinishing pigs. However, Samanta et al [44] found that organic chromium increased moisture levels and decreased crude fat contents in meat of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…However, many studies have shown that dietary Cr supplementation caused a positive effect on growth performance and carcass traits of broilers [3][4][5][6][7][8]. Chromium, as well, could affect lipid metabolism and reduce body fat deposition of broilers [9][10][11]. The benefits of Cr supplementation are mostly observed under stressful conditions, and this may be attributed to the effect of Cr in reducing stress-induced corticosteroid concentrations [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%